Penerapan Manajemen Dakwah dalam Meningkatkan Motivasi Anggota Mengikuti Pengajian di Majelis Taklim Al-Ikhlas Kelurahan Pahlawan - Usnatul Ayni; Anang Walian (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study aims to determine the Implementation of Da'wah Management in Increasing the Motivation of Members of the Al-Ikhlas Taklim Assembly to Follow the Study at the Al-Ikhlas Taklim Assembly, Pahlawan Village, Kemuning District, Palembang City. This research was conducted at the Al-Ikhlas Taklim Assembly, Pahlawan Village, Kemuning District, Palembang City. The type of research used is descriptive research, the method used in this study is by observation and interview. This study consists of two types of sources, namely primary data and secondary data. To obtain data properly and as expected, relevant methods are used. Data analysis is an effort to achieve and systematically organize records of interview results, observations, and other documentation. To improve the researcher's understanding of the case being studied and make it a finding for others. Interactive analysis techniques according to Miles and Huberman are analysis techniques used to identify, categorize, and interpret qualitative data. Based on the results of the research conducted on the application of da'wah management in increasing the motivation of members of the taklim assembly to attend religious studies at the Al-Ikhlas Taklim Assembly, Pahlawan Village, Kemuning District, Palembang City and after going through the discussions that have been presented in the previous chapters supported by existing data and theories, it can be concluded that: The application of da'wah management at the Al-Ikhlas Taklim Assembly, Palembang is running well with effective planning, organizing, and evaluation, thus increasing the motivation of members to attend religious studies. Supporting factors for motivation include the desire to deepen religious knowledge, a comfortable environment, and relevant materials. Meanwhile, the inhibiting factors are concurrent activities and bad weather. Members of the taklim assembly are motivated to increase their faith, friendship, and be a good example for their families.